Penerapan ERP pada Perusahaan Manufaktur Konveksi Bali Valentine Menggunakan Aplikasi Dolibarr - Luh Dyah Pradnya Wulandari; Dwi Putra Githa; Gusti Agung Ayu Putri (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Konveksi Bali Valentine is a manufacturing company engaged in clothing or textiles. The system used by this company is to make orders, namely products that will be made if there is an order from a customer. Konveksi Bali Valentine often experiences problems when managing raw materials in the production process, compiling documentation, making production reports, recording purchases of raw materials from suppliers, and recording product sales to customers who are still conventional, where the ordering process is recorded manually so that the company has data that is temporary. The objectives of this research is to find out the business processes that are running at the Konveksi Bali Valentine company, implement the Enterprise Resource Planning (ERP) system, and find out the appropriate proposed business processes. Analysis of business processes that are being carried out by direct observation to the company. ERP implementation focuses on the production, purchasing, sales, and warehouse processes using the Dolibarr application and the Accelerated SAP method consisting of project preparation, business blueprint, realization, final preparation, and go live and support. ERP system testing at the final preparation stage uses the User Acceptance Test (UAT) method. Keywords— Konveksi Bali Valentine, ERP, Dolibarr, Accelerated SAP